Social networks and their importance in job searching of college students - Potkány, Marek; Hajduková, Alexandra (Business: Theory and Practice, 2015)
At present, in every sphere of human activity, using modern ICT is considered as a matter of course. Several human resources management institutions are aware of the potential of social networks in estabilishing and building relationships with their target groups. It is a trend to create job portals in social networks. These are currently an integrated part of communication with target audience and therefore also an objects of attention and reflexions. It is also the topic of this paper. The goal of this research is to determine the level of use of social networks by college students in Slovakia. Part of the research is also to discover the effect of social networks on job searching of a selected sample of students. The research was conducted on a sample of 407 slovak students. A questioning method in form of an online questionnaire was used. The obtained results were processed using methods of descriptive and test statistics. We studied the significance of gender on the frequency of using the internet to search for job opportunities via social networks, as well as the ability to apprehend the importance of personal presentation on social networks. The statistical testing did not prove any significant difference between men and women in the question of frequency of using internet to search for job opportunities, nor in the ability to apprehend the importance of personal presentation on social networks. A statistically significant difference in gender was proven only in case of using social networks in job searching. Women tend to use social networks to find jobs more often than men. These statements are proved by the results of tests of significance of mean changes at the 5% significance level, which means that they are valid with 95% probability.